Sprawl and suburbia : a Harvard design magazine reader - Saunders, William S. (Harvard design magazine readers ;, 2005)
Sprawl and Suburbia brings together some of the foremost thinkers in the field and calls for architects, urban planners, and landscape designers to work at mitigating the impact of sprawl and improving the built environment as a whole.